Second-Order Sliding Mode Control of Three-Phase Three-Level Grid-Connected Neutral Point Clamped Inverters - Altın, Necmi N.; Ozdemir, Saban S.; Sefa, Ibrahim; Komurcugil, Hasan (Institute of Electrical and Electronics Engineers Inc., 2021)
In this paper, a second-order sliding mode control method is proposed for three-phase three-level grid-connected NPC inverter. The proposed second-order sliding mode control is based on super twisting algorithm which provides fast transient response and robustness to the system uncertainties and disturbances which are very important features for grid-connected inverter applications. Unlike ordinary sliding mode control, it provides continuous control feature which is easy to apply. Furthermore, the proposed approach also provides constant switching frequency and removes the chattering problem which may even cause saturation if no action is taken. The performance of the suggested control system with the three-phase three-level NPC inverter is confirmed with simulation studies. It is obviously seen that the proposed system has fast response without overshooting and oscillation. Besides, the THD level of the current injected to the grid is obtained as 1.1%. © 2021 IEEE.
13th International Conference on Electronics, Computers and Artificial Intelligence, ECAI 2021 -- 2021-07-01 through 2021-07-03 -- Pitesti -- 171421
Keywords: grid-connected inverter; neutral-point-clamped inverter; sliding mode control; Super twisting algorithm